PERLINDUNGAN HUKUM TERHADAP PEMENANG LELANG YANG BERITIKAD BAIK ATAS GUGATAN PERLAWANAN DEBITOR PEMBERI JAMINAN HAK TANGGUNGAN YANG TELAH DILELANG OLEH BANK (STUDI PUTUSAN MAHKAMAH AGUNG NO. 3564.K/PDT/2015) - ALWINE ROSDIANA PAKPAHAN (PREMISE LAW JURNAL, 2017)
A loan agreement with mortgage is performed by a bank as the creditor; thus, when a debtor is default in paying the creditor, the creditor possesses the right to execute the mortgage object with his own power after firstly requesting for fiat yustitsia to the head of the district court in the area where the mortgage object lies. This is a normative legal research done by reviewing the law and regulations i.e. Law No. 10/1998 on Banking and Law No. 4/1996 on Mortgage and Bidding Regulation in this research. This is a descriptive analytical research which describes, explains and analyzes problems and finds answers to solve them. The results of the consideration of the cassation appeal judges of the Supreme Court for the complaint filed by the debtor of the mortgage in the Ruling of the Supreme Court No. 3564.K/PDT/2015 is that the cassation appeals filed by the plaintiff I named Z and plaintiff II named S do not have clear legal ground, and the mortgage object is acquired by the mortgage bidding winner through the prevailing procedures and legal provisions so that the possession of the mortgage object is valid, has legal force and has to be legally protected.Keywords: Legal Protection, Bidding Winner, Mortgage Object